Capillary Electrophoresis Methods and Protocols - Schmitt-Kopplin, Philippe (Methods in Molecular Biology, 2016)
This new edition presents principle methods in capillary electrophoresis (CE) separation involving CZE, MEKC, MECC, NACE, and corresponding hyphenated techniques to organic mass spectrometry and ICP-MS. Recent developments in the techniques of single cell analysis, as well as derivation, enantioseparation or the use of ionic liquids, and the use of CZE for the separation of living cells are also highlighted. This book discusses various application methods for the analysis of small ions, organic acids, amino acids, and (poly)saccharides to peptides that are shown with pollutants and biomarkers in food and health. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting edge and thorough, Capillary Electrophoresis: Methods and Protocols, Second Edition covers a wide field of interests and will be especially great for beginners and students because of its combined focus on mini-reviews and application notes that will help them quickly get an overview of the field